144 DEVELOPING AN INTEGRATED POST DIAGNOSTIC PATHWAY FOR PERSONS LIVING WITH DEMENTIA—EXPERIENCES OF A REGIONAL SPECIALIST MEMORY SERVICE. (18th November 2021) - McHale, C; Fallon, A; Domsa, M; McGuinn, C; Tobin, F; Sheridan, L; Dookhy, J; Coughlan, T; O'Neill, D; Kennelly, S
Abstract: Background: The frequently heterogeneous nature of a dementia presentation confers the need for a personalised approach to post-diagnostic supports. It's an essential right for persons living with dementia (PlwD) and their families/supporters to have access to a comprehensive diagnosis and a responsive holistic pathway of care thereafter. We report our development of an integrated specialist-clinic/community post-diagnostic pathway responsive to the evolving personal needs of PlwD and their care-supporters. Methods: This pathway was developed in an iterative inclusive-design methodology with input from hospital/community clinical specialists, health and social care professionals, senior nursing, PlwD and their care supporters. The post-diagnostic process starts at diagnosis disclosure, followed for all six-weeks later with a designated post diagnostic clinic, where a single point of contact to address any concerns in between visits is established. Results: Iterative review cycles have identified integral components of an effective pathway: Guidance to live well with their personal manifestation of dementia; Acknowledgment of biopsychosocial elements of care; Timely access to comprehensive geriatric assessment via ambulatory hub MDT and/or and Integrated care team for older persons offering home assessment & intervention; Prevention of 'harmful-events' e.g. falls/delirium/hospitalisation; Timely access to therapies e.g. SLT/OT focussed on enhanced life at home/assistive technology; facilitation and planning of palliative care. Other aspects include signposting to community resources and forward planning e.g. Citizen's Information Centres; Peer support and education through designated training; Promotion of brain health- Exercise Programmes; social/cognitive stimulation e.g. Men's sheds, Walking groups & Memory Resource Rooms; Opportunities for research involvement; Enhanced relationships with national organisations e.g. embedded ASI dementia advisor. Conclusion: This approach has developed into a fully integrated holistic care-pathway where specialist-clinic, ambulatory-hospital, community older persons, and third sector services work together to provide the right care, at the right time, in the right place for PlwD and their families.